PI-RADSv2.1 combined with PSA density for optimizing prostate biopsy decisions: a retrospective analysis - Li, Yuchun; Wang, Siran; Wang, Jianqiu; Qi, Xin; Liu, Tianran; He, Xiaodong; Zhang, Yu; Zhu, Yi; Zeng, Yunfu (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to explore the application value of the Prostate Imaging Reporting and Data System version 2.1 (PI-RADS v2.1) combined with prostate-specific antigen density (PSAD) for guiding prostate biopsy, with the goal of improving biopsy positivity rates and reducing unnecessary procedures.MethodsA retrospective analysis was conducted on data from 462 patients (44-89years) who underwent prostate biopsy. Univariate and multivariate logistic regression analyses were used to identify independent risk factors for clinically significant prostate cancer (csPCa). Independent risk factors were explored to establish a diagnostic model for csPCa and indications for prostate biopsy. The diagnostic performance was evaluated by receiver operating characteristic (ROC) curve analysis, assessing sensitivity, specificity, positive predictive value, negative predictive value, biopsy avoidance rate, and missed diagnosis rate.ResultsUnivariate and multivariate logistic regression analyses indicated that PI-RADS v2.1 score [P < 0.001; odds ratio (OR) =9.779; 95% confidence interval (CI) = 5.849-16.349] and PSA density (PSAD) [P < 0.001; OR = 6.128; 95% CI = 2.292-16.386] were independent risk factors for csPCa. The combined PI-RADS v2.1 and PSAD approach exhibited excellent diagnostic performance (AUC = 0.966), with sensitivity and specificity of 92.4% and 91.6%, respectively. The threshold for diagnosing csPCa was a PI-RADS v2.1 score of ≥ 4 and PSAD ≥ 0.30 ng/(mL·cm³). Specifically, no csPCa was detected among patients with PI-RADS ≤ 2 and PSAD < 0.30 ng/(mL·cm³), indicating these biopsies could be safely avoided. Similarly, for patients with a PI-RADS v2.1 score of 3 and PSAD < 0.15 ng/(mL·cm³), the csPCa detection rate was also zero, supporting biopsy avoidance in these cases.ConclusionThe use of the PI-RADS v2.1 score combined with PSAD is recommended as an indication for prostate biopsy: (1) For patients with PI-RADS scores of 1-2, biopsy can be avoided if PSAD is < 0.30 ng/(mL·cm³), whereas biopsy is recommended if PSAD is ≥ 0.30 ng/(mL·cm³). (2) For patients with a PI-RADS score of 3, biopsy can be avoided if PSAD is < 0.15 ng/(mL·cm³), but it is recommended if PSAD is ≥ 0.15 ng/(mL·cm³). (3) Patients with a PI-RADS score of 4 are recommended for biopsy in all cases. (4) For patients with a PI-RADS score of 5, biopsy is recommended if PSAD is < 2.00 ng/(mL·cm³), but empirical initiation of treatment without biopsy may be considered if PSAD ≥ 2.00 ng/(mL·cm³), subject to ethics committee approval. Using these criteria, 40% (186/462) of patients in this study could potentially avoid prostate biopsy.